The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fsurg.2022.844993
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy for the Treatment of Glioblastoma: A Review

Abstract: BackgroundPhytotherapy; the study of extracts of natural origin in the treatment of disease, has scarcely been applied in the management of GBM. A body of literature exists studying in-vitro, the use of natural extracts against GBM cells. Given persisting poor prognoses, we evaluated, through systematic literature-review the therapeutic potential of naturally sourced extracts in-vivo.MethodsUsing OVID, MEDLINE and EMBASE databases were searched with compound search term. Abstracts and full-texts were double-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[4, 5] Most GBM exhibit EGFR amplification, however EGFR inhibitors have failed in clinical trials due to intratumoral heterogeneity and poor blood-brain-barrier (BBB) permeability. [4, 5] Furthermore the modulation of BBB by glioma stem cell transcription factors confer to GBM chemoresistance [46] Currently there is a significant lack of treatment options for GBM and several novel therapeutics approaches [4, 28] including phytochemicals [35] are being explored. Hence to address this therapeutic gap, having established the merit of targeting SERPINE1 for the treatment of GBM, in this study we propose potential lead-like molecules derived from Calotropis gigantea which can be developed for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…[4, 5] Most GBM exhibit EGFR amplification, however EGFR inhibitors have failed in clinical trials due to intratumoral heterogeneity and poor blood-brain-barrier (BBB) permeability. [4, 5] Furthermore the modulation of BBB by glioma stem cell transcription factors confer to GBM chemoresistance [46] Currently there is a significant lack of treatment options for GBM and several novel therapeutics approaches [4, 28] including phytochemicals [35] are being explored. Hence to address this therapeutic gap, having established the merit of targeting SERPINE1 for the treatment of GBM, in this study we propose potential lead-like molecules derived from Calotropis gigantea which can be developed for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…A strong and reliable correlation was found between the antioxidant and anticancer activities of different plant extracts [22,23]. Therefore, it should be assumed that bearberry leaf extracts, which, in previous studies showed antioxidant activity due to the presence of arbutin, hydroquinone, methylarbutin, hyperoside, and flavonoids [19,24,25], will also be active against glioblastoma, which is one of the most perplexing cancers with one of the worst prognoses in modern medicine [26]. Therefore, the use of diversified raw materials and various extractant types is justified because the varied chemical composition of extracts determines their biological activity.…”
Section: Introductionmentioning
confidence: 92%
“…Systemic delivery of anti-miR-21 resulted in reduced proliferation, tumor growth inhibition, and increased apoptosis in a mouse model of GBM [ 204 ]. Lipid nanoparticles containing miR-124 have been found to prolong survival, prevent tumor recurrence, and induce immune memory [ 53 , 205 , 206 , 207 , 208 , 209 ].…”
Section: The Use Of Mirnas In Gbm Therapymentioning
confidence: 99%